Improving Descriptive Speaking Skills By Implementing Project-Based Learning Using Flashcards and Mind Maping - Nur Afifah Saktiana Indahwati; Lidwina Sri Ardiasih2; Udi Samanhudi (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to improve descriptive speaking skills by implementing project-based learning using flashcards and mind mapping. The main purpose of this research was to describe improving descriptive speaking skills by implementing Project-based learning using flashcards and mind mapping for Seventh Graders of SMP Negeri 2 Modung Bangkalan in The Academic Year 2022/2023. To know about it, the researcher used some instruments such as observation and tests. After analyzing the data and counting the scores of students’ skills in tests, the researcher found that there were significant differences before and after the treatment. It meant that there was improving descriptive speaking skills by implementing Project-based learning using flashcards and mind mapping. To support those results, the researcher used a t-test formula to count the test results. To start calculating the data, the researcher counted the mean and the standard deviation in every Pre-test and Post-test from the experimental class and control class. Then, the result was entered into the formula. The research counted the t-table by calculating df and determined the percentage of significance. After that, the result of the t-test is compared with t-table to answer the hypothesis.